Influencing policy and practice is work in progress - Nelson, Elizabeth; O'Reilly, Dermot (International Journal of Population Data Science, 2022)
Focusing on policy impact without a functioning regional devolved government required Administrative Data Research Centre Northern Ireland (ADRC NI) researchers and staff to develop new ways of influencing policy and practice in Northern Ireland. The development of a co-production model with policymakers, service providers and third sector representatives has embedded pathways to impact within research programmes, to great success. This paper describes the efforts of the ADRC NI to influence policy and practice, in Northern Ireland in challenging political circumstances, outlining the context, approach, processes, strengths, challenges and lessons for the future.